PELATIHAN MENUMBUHKAN APRESIASI SASTRA MELALUI MENGAPRESIASI KRITIK SASTRABAGI MGMP BAHASA INDONESIA SMA SE-SURABAYA - Indayani; M. Shoim; Sunu Catur Budiyono (Universitas PGRI Adi Buana Surabaya, 2026)
This community service aims to foster an appreciation of literature among senior high school Indonesian language teachers through activities that encourage literary criticism. Many teachers still face obstacles in appreciating literary criticism. Until now, literature learning in secondary schools has tended to focus on understanding the intrinsic elements of literary works, while literary criticism has been underutilised as a means of deepening meaning and developing an appreciative attitude. The Community Service (PkM) programme of the Indonesian Language Education Study Programme at PGRI Adi Buana University in Surabaya seeks to address this challenge through training to foster literary appreciation through literary criticism for the Indonesian Language Teacher Working Group (MGMP) of senior high schools in Surabaya. This training will take place from 14 November to 12 December 2025. The community service activities were carried out in the form of presentations and mentoring, which included an introduction to the concept of literary criticism, analysis of examples of literary criticism, and practice in appreciating literary works from a critical perspective. The results of the activities showed an increase in teachers' understanding of literary criticism. In addition, it also fostered an appreciative attitude towards literary works and improved the quality of literature learning in senior high schools.